Peculiarities of metal welding process modelling for the Arctic - Lagunov, Alexey; Fofanov, Andrey; Losunov, Anton (AIP conference proceedings, 2017)
M etal being rather tough has been used in the Arctic for a long time. In severe weather conditions metal construction is subject to strong corrosion and erosion. These processes affect the welds particular strongly. Violation of weld integrity leads to the different industrial accidents. Therefore, the welding quality is given such a strong focus. M ost high-quality welding is obtained if welding zone is provided with gas what eliminates the influence of oxygen on the process. But in this case it is very difficult to find the right concentration, gas pressure, direction of the jet. Study of the welding process using video and photography is expensive, in terms of money and time. Mathematical modelling of welding process using the program FlowVision enables to solve this issue at less cost. It’s essential that obtained results qualitatively conform to the experimental ones and can be used in real application.